Автобіографія: витоки, становлення та критика жанру - Малішевська, І. (Літературознавчі обрії. Праці молодих учених, 2010)
The essence of autobiography as a genre is examined. And critical studies on autobiography, particularly by Philippe Lejeune and feminist school are reviewed. The author reveals the problem of defining the genre of autobiography and investigates motives for writing about the self.